What's left of the radical left online? Absence of communication, political vision, and community in autonomist web milieus in Sweden. (January 2018) - Andersson, Linus
This article presents and discusses results from a study of radical left-wing activism online carried out by the Swedish Media Council, a report that suggested that the Internet (i.e. the web, web 2.0, and social media) is not a prioritized arena for propaganda and recruitment for the radical left in Sweden. The purpose of this article is to re-evaluate some of these findings and add to the discussion on online activity and connectivity in political communication online, as well as to problematize simplified notions of radicalization and recruitment to pro-violent groups. Based on a hermeneutic inquiry regarding modes of communication, representations of political visions, and community, the article shows how the sites and groups studied favor one-way communication before interactivity, that political visions are limited to short-term goals in the immediate future, and that they give very little information about their activist activities to recruit supporters.